Efeitos agudos de diferentes intensidades de exercício resistido sobre os ajustes vasculares em artéria mesentérica de ratos - Mota, Marcelo Mendonça (2014)
The direct relationship between resistance exercise and vascular health is certain, but the complex set of metabolic and hemodynamic pathways and the effects of this type of exercise on cardiovascular tissues are still controversial. Although consensus that nitric oxide (NO) contributes to the control of blood flow during resistance exercise, are not yet fully understood the events signaling in the vasculature that mediate the release of this vasoactive agent. In this sense, the objective of the present study was to evaluate the acute effects of different intensities of resistance exercise on vascular adjustments in the superior mesenteric artery of healthy rats. The thesis comprises two chapters, consisting of two original articles. The first article, "Resistance exercise enhances insulin mesenteric artery acutely-induced relaxation in healthy rats", which assessed the acute effects of an exercise session held on vascular actions of insulin in rat mesenteric artery. In this first study, it was observed that a resistance exercise session increased the vasorelaxation via PI3K/eNOS. Such increase is due in part to an increased production of NO, associated with an increase in the participation of channels for K+ and Na+/K+-ATPase. The second article, "Endothelium adjustments to acute resistance exercise are intensity-dependent in healthy animals", demonstrated that a session of vigorous exercise moderately weathered and/or improves endothelium-dependent relaxation induced by insulin due to an increase in the levels of phosphorylation of eNOSser1177 and, consequently, increased endothelial production of NO healthy animals. From these findings it is possible to suggest that resistance exercise promotes vascular adjustments that work in favor of better control of vascular tone. In addition, the magnitude of these beneficial vascular adjustments is strongly related to increased resistance exercise intensity from the intensity of 50% of 1 RM.